IoT intelligent money box / Mohamad Hilman Shoib - Shoib, Mohamad Hilman (2024)
Effective money management and instilling saving habits from an early age are crucial for financial well-being. However, the lack of emphasis on saving during childhood and poor money management skills pose significant challenges. In this study, we propose an IoT-based money box system that incorporates automatic recognition of coins and notes. The methodology involves utilizing an Arduino MEGA as a microcontroller along with main sensors such as a Coin Acceptor and a Color Sensor. The system enables real-time monitoring of the money balance and setting goals for savings by using a user interface or a cloud platform. By leveraging IoT technologies, this solution aims to improve money-saving habits and enhance financial management skills. The collected data is processed to provide effective results: the Color Sensor detects notes insertion, the Coin Acceptor detects coin insertion, and the balance is displayed through an LCD and the Blynk app. Through the implementation of automatic recognition and monitoring features, individuals can nurture better saving practices and maintain a track record of their finances. This research contributes to the advancement of IoT-based approaches in promoting responsible financial behaviour and empowering individuals with improved money management skills